Pharmaceutical Office for care of Hiperdia patients in Primary Health Care in the Municipality of Benevides, Pará (Research, Society and Development, 2024)
Objective: To present the Pharmaceutical Office for Patient Care of Hiperdia in Primary Health Care in the city of Benevides, Pará. Methodology: This is an experience report on the process of implementing the Pharmaceutical Office for Patient Care of Hiperdia in Primary Health Care in the city of Benevides, Pará. Conclusion: It can be inferred that the implementation of the Pharmaceutical Care Office has the potential to promote the correct and quality use of medications; thus contributing to the control of chronic non-communicable diseases, such as Hypertension and Diabetes, promoting the improvement of quality of life, the reduction of health damage and the reduction of costs for the Unified Health System.